(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Palatal rugae or plicae palatine are uneven ridges made of connective tissue situated beneath the incisive papilla. DNA analysis, finger prints analysis, are the most common techniques used for establishing person’s identity but in situation where using these techniques are difficult palatal rugae can be used as a second source of identification. However, some habits like prolonged thumb sucking and orthodontic treatment for long duration could affect the rugae pattern. Hence, this study aims to evaluate the changes in transverse dimensions of palatal rugae in subjects treated with rapid maxillary expansion Material and Methods: The palatal rugae patterns were measured and compared to evaluate the morphometric changes between pre-treatment cast (30 Pre-RME) and its post-treatment (30 Post-RME) counterpart. All pre-and post-expansion dental casts were traced and the intermedial and interlateral dimensions of first, second and third rugae were measured. The statistical analysis was done using paired t test. Conclusion: The medial aspect of first primary rugae can be considered as a stable reference landmark while the lateral and medial aspects of the 2nd and 3rd rugae are liable to changes in transverse dimension. Hence, for forensic identification the stability of palatal rugae in patients who had undergone rapid maxillary expansion still remains questionable